PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV TUNARUNGU SLB NEGERI DUMAI - Suratmi '; Gustimal Witri Witri; Hendri Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is conducted because of low achievement of Math subject of fourth grade Deaf students. Minimum completeness criteria (KKM) of Mathematics is 65, from the 12 students only 4 students (33,33%) passed the 65 minimum completeness criteria. The formulation of the problem in this study is whether the application of direct instruction can improve the result of the fourth grade Deaf students in learning math in SLBN Dumai. The purpose of this research is to improve students’ achievements in Math through the application of direct instruction. This study uses action research through direct instruction of 12 deaf students in fourth grade in SLBN Dumai. This study was completed in April 2014. The initial results of this research, only 4 students (25%) achieved a minimum completeness criteria which is 65. After applying direct instruction in the classroom, at UH I cycle I the number of students who pass the minimum completeness criteria increased to 9 students (75%). UH II In cycle 2, the number of students who achieve a minimum completeness criteria also increased to 10 students (83,3%). So the hypothesis of this research “whether the application of direct instructional model can improve the results of the fourth grade deaf students  in learning math in SLBN Dumai” is acceptable. Key Words       : Direct Instruction, Students’ Achievement in Math